COMPARATIVE ANALYSIS ОF GEOMETRIC DEVIATIONS IN CONTACT MEASURING INSTRUMENTS FOR CONTROL AND LASER CONTACTLESS SCANNING (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The factors affecting the dimensional accuracy of 3D scanning using a measuring arm with an integrated scanner and a custom open source 3D printer using FDM technology are researched in this paper, with the purpose of isolating and reducing the sources of errors affecting the results. A consumer 3D printer is analyzed in terms of achieving accurate physical dimensions, consistent shapes, and predictable surface coverage.